Preparation and Characterization of Carboxymethyl Cellulose Production from Oil Palm Male Inflorescence as Food Stabilizer - Jainal, Rahmat; Madusari, Sylvia; Sari, Vira Irma; Putri, Halida Adistya; Febriana, Dela (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Male inflorescence residue of the oil palm rich in fibre and contains cellulose content and has the potential to synthesize Carboxymethyl Cellulose (CMC). Male inflorescence is considered necessary removed in the early stages of the oil palm cultivation process to develop stem size, string and robust root systems. This activity generates plentiful of oil palm male inflorescence residues in the plantation. The aim of this research is to synthesis and characterize CMC fabricated from oil palm male inflorescence (OPMI-CMC) waste for use as an ice cream stabilizer, using a variety of treatments, which are commercial CMC 0.2%, OPMI-CMC 0.1%, 0.2%, and 0.3%. The results showed that CMC can be produced from organic waste of male flowers of oil palm plants. The water content, pH, purity, and degree of substitution meet the standard. The optimal concentration of OPMI-CMC for ice cream stabilizer is 0.3% based on melting time and overrun value. The FTIR analysis shows that the main functional group of the OPMI-CMC is highly comparable. Therefore, to possibly be employed as an alternative to organic CMC for food stabilizers, other standards must be fulfilled, and further research is required.